2014
DOI: 10.1007/s13762-013-0469-8
|View full text |Cite
|
Sign up to set email alerts
|

Competitive adsorption of dye species from aqueous solution onto melon husk in single and ternary dye systems

Abstract: Polluted water may contain more than one dye species. Consequently, the behavior of a particular dye in a water system may be affected by the presence of the others. In this study, the adsorption of methylene blue (MB) in single dye system (SDS) and in ternary dye system (TDS) comprising of MB, congo red and methyl orange onto formaldehyde-treated melon husk (FMH) was investigated as a function of pH, contact time and species concentrations. Surface studies of FMH were investigated by Fourier transform infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 41 publications
(40 reference statements)
1
28
1
1
Order By: Relevance
“…Removal or disposal of dye is a crucial task for environmental aspects. The production of large amounts of dye results in requirement of low‐cost removal methods . The efficient removal methods with high energy requirements are not generally appropriate for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Removal or disposal of dye is a crucial task for environmental aspects. The production of large amounts of dye results in requirement of low‐cost removal methods . The efficient removal methods with high energy requirements are not generally appropriate for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The main drawback of high dye concentrations in effluents are low penetration of light to deeper parts of water resources. [5][6][7][8][9] The unfixed colorants and auxiliaries of textile industries are the main sources of dye effluents. [10] Removal or disposal of dye is a crucial task for environmental aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that increasing the dye's concentration from 10 to 100 mg · L −1 , lead to a decrease in removal efficiency from 97.51 to 79.76 % (Figure ). Such observations can be explained by the fact that the biosorbent has limited numbers of active sites, which become saturated above a certain concentration . It is observed that the removal efficiency increases by increasing the contact time (Figure ).…”
Section: Resultsmentioning
confidence: 94%
“…Among these techniques, adsorption is attracting increasing interest due to its properties of simple operation, high performance, and low running cost [16][17]. Both natural and synthetic materials have been used as adsorbents to remove dyes from wastewater [18][19]. As natural clay, bentonite has been used widely as an adsorbent for much pollutant removal, including PPCPs, heavy metal, VOCs, etc.…”
mentioning
confidence: 99%